Analisis Maslahah Mursalah Menurut Imam Al-Ghazali terhadap Peraturan Pemerintah No 36 Tahun 2021 tentang Pengupahan - Nadiya Ratna Pura; Panji Adam Agus Putra; Ira Siti Rohmah Maulida (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. The current regulation regarding wages is regulated in Government Regulation No. 36 of 2021 concerning Wages, the principle of providing wages in Islam must be based on justice and feasibility by reviewing aspects of life that aim to achieve welfare both in the world and in the future in the Hereafter. The purpose of preparing this study is to find out the suitability of the concept of maslahah mursalah according to Imam Al-Ghazali to PP Number 36 of 2021 concerning Wages. This research uses a normative juridical approach, with the type of research, library research, the source of this research data is primary and secondary sources, The data collection technique uses literature methods as well as interviews. The result of this study is that PP No. 36 of 2021 concerning Wages is in accordance with the concept of maslahah mursalah according to Imam Al-Ghazali because one of the conditions for the hujjahnya maslahah mursalah according to Imam Al-Ghazali is the achievement of human dharuriyyah needs, PP No. 36 of 2021 has paid attention to the interests of religion, soul, reason, descendants, and property to achieve the welfare of workers/laborers, as in Article 43 which regulates wage protection for employees who do not enter work because of religious obligations Abstrak. Pengaturan mengenai pengupahan saat ini diatur dalam Peraturan Pemerintah No 36 Tahun 2021 Tentang Pengupahan, prinsip pemberian upah dalam Islam harus berdasar kepada keadilan dan kelayakan dengan meninjau aspek kehidupan yang bertujuan untuk mencapai kesejahteraan baik di dunia dan kelak di akhirat. Tujuan penyusunan penelitian ini yaitu agar mengetahui kesesuaian konsep maslahah mursalah menurut Imam Al-Ghazali terhadap PP Nomor 36 Tahun 2021 Tentang Pengupahan. Penelitian ini menggunakan pendekatan yuridis normatif, dengan jenis penelitian, penelitian Pustaka, sumber data penelitian ini adalah sumber primer serta sekunder, Teknik pengumpulan datanya menggunakan metode kepustakaan serta wawancara. Hasil penelitian ini ialah PP No 36 Tahun 2021 Tentang Pengupahan telah sesuai dengan konsep maslahah mursalah menurut Imam Al-Ghazali karena salah satu syarat hujjahnya maslahah mursalah menurut Imam Al-Ghazali ialah tercapainya kebutuhan dharuriyyah manusia, PP No 36 Tahun 2021 telah memperhatikan kepentingan agama, jiwa, akal, keturunan, serta harta untuk mencapai kesejahteraan para pekerja/buruh, seperti dalam Pasal 43 yang mengatur mengenai perlindungan upah atas pegawai yang tidak masuk bekerja karena menjalankan kewajiban beragama.